Problems of Harmonization of the Legislation of Kazakhstan and China - Participants of Strategy «A Silk Way» - A, Guiguo Wang; L., Baideldinov D.; F, Bekturova A. (Farabi Journal of Social Sciences, 2019)
Abstract. Given article is devoted to the problems of unification of the legislation of Kazakhstan and China on the question of transnational transaction of products and services. Also analyzing main conditions of Kazakh-Chinese relations and their legal regulation is conducted. As a foundation of given relations are taken conditions of the realization of the strategy «One Belt and One Road». As a feature of the development of Kazakh-Chinese relations, their realization in the frames of Eurasian Economic Community is discussed. Authors analyze activity of this EEC, customs and emigrational policy, economic relations. In addition, they set down possibilities of realization of the given scheme in the frames of strategy «One Belt and One Road».